Neutrophil-To-Lymphocyte Ratio as a Prognostic Indicator in Thyroid Cancer - Qiangang Gao MMS; Mingming Quan MMS; Lilong Zhang PhD; Yanyun Ran MMS; Jijun Zhong MMS; Bin Wang MMS (Cancer Control)
Objective In this study, we aimed to perform a comprehensive analysis to assess the prognostic value of neutrophil-to-lymphocyte ratio (NLR) levels in patients diagnosed with thyroid cancer. Methods We systematically searched multiple databases, including PubMed, the Cochrane Library, EMBASE, and Google Scholar, up until March 30, 2023, to identify relevant articles. The clinical outcomes evaluated in this study included overall survival (OS), progression-free survival (PFS), disease-free survival (DFS), and cause-specific survival (CSS). Results This analysis includes 21 articles with 5187 patients in total. The pooled results revealed that patients with high NLR levels had significantly poorer OS (HR: 2.578, 95% CI: 2.050-3.242, P < 0.001), PFS (HR: 2.143, 95% CI: 1.616-2.843, P < 0.001), DFS (HR: 1.377, 95% CI: 1.045-1.816, P = 0.023), and CSS (HR: 2.842, 95% CI: 1.334-6.053, P = 0.007). The subgroup analyses were performed based on different study regions, treatment modalities, cancer types, and NLR cut-off values, and the above conclusion remained consistent in the majority of subgroup analyses. The stability and reliability of the aforementioned results were supported by the sensitivity analysis and publication bias test. Conclusion The baseline NLR levels were useful predictors of outcomes in patients with thyroid cancer.